Critical appraisal and data extraction for systematic reviews of prediction modelling studies : the CHARMS checklist - Moons, K; de Groot, J; Bouwmeester, W; Vergouwe, Y; Mallett, S; Altman, D; Reitsma, J; Collins, G (Public Library of Science, 2014)
Carl Moons and colleagues provide a checklist and background explanation for critically appraising and extracting data from systematic reviews of prognostic and diagnostic prediction modelling studies. Please see later in the article for the Editors' Summary.